Cancer-Related Debt and Mental-Health-Related Quality of Life among Rural Cancer Survivors: Do Family/Friend Informal Caregiver Networks Moderate the Relationship?. (March 2020) - Hallgren, Emily; Hastert, Theresa A.; Carnahan, Leslie R.; Eberth, Jan M.; Mama, Scherezade K.; Watson, Karriem S.; Molina, Yamilé
Social connectedness generally buffers the effects of stressors on quality of life. Is this the case for cancer-related debt among rural cancer survivors? Drawing on a sample of 135 rural cancer survivors, we leverage family/friend informal caregiver network data to determine if informal cancer caregivers buffer or exacerbate the effect of cancer-related debt on mental-health-related quality of life (MHQOL). Using data from the Illinois Rural Cancer Assessment, a survey of cancer survivors in rural Illinois, we estimate the association between cancer-related debt and MHQOL and whether informal caregiver network size and characteristics moderate this association. Over a quarter of survivors (27%) reported cancer-related debt, and those who did reported worse MHQOL. However, this association only held for survivors who had an informal caregiver network. These findings supplement what is already known about the role of social connectedness in cancer survivors' health outcomes. We offer possible explanations for these findings.